GAMBARAN PERILAKU MASYARAKAT DALAM PELAKSANAAN PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN COVID-19 DI WILAYAH KERJA PUSKESMAS WAJO - Hasniati Hasniati; Waode Azfari Azis; Wahyuddin Wahyuddin; La Ode Muh Taufiq (Kampurui Jurnal Kesehatan Masyarakat, 2023)
Efforts prevent spread Covid-19 can be carried out with strict health protocols and carried out by all levels society. Data from Wajo Health Center showed many as 202 cases Covid-19 and there are 2 cases death in 2021. Increase in cases Covid-19 is caused not complying with health protocols recommended by government. Purpose study was to find out description behavior in form washing hands, wearing masks, maintaining distance, staying away from crowds, and reducing mobility in implementation health protocols effort to prevent Covid-19. Type of research used is descriptive observational. Research population is entire community totaling 18,532, sample amounting to 391 and side method used is cluster sampling. Research data collection consisted primary data obtained by questionnaire and secondary data obtained from report notes Wajo Health Center. Data processing is done computerized using SPSS program. Analysis used is univariate analysis, namely to see appearance frequency distribution each variable studied. Results univariate analysis showed that 59.6% had poor hand washing behavior, 59.6% had less mask wearing behavior, 55.8% had less social distancing behavior, 55.5% avoided crowd behavior who are lacking, and 57.5% have behavior of reducing mobility that is lacking in implementation health protocols as an effort to prevent Covid-19. Conclusion shows that there is still a lack community behavior in implementing health protocols effort to prevent Covid-19 in work area Wajo Health Center, Baubau City. Suggestions for need to increase awareness, willingness and behavior from the community to implement health protocols effort to prevent Covid-19.